Pengaruh Transformational Leadership, Motivation, Career Development dan Work Environment Terhadap Employee Performance Melalui Job Satisfaction Sebagai Variabel Mediasi di BUMN XYZ Tahuna - Christian Dwijaya Rorora; Jacquelinda Sandra Sembel (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research investigates the impact of transformational leadership, motivation, career development, and work environment on employee performance, using job satisfaction as a mediator. We used the cross-sectional method to obtain quantitative data through an online questionnaire. We obtained all demographic data from 108 employees of BUMN XYZ Tahuna who had worked for at least one year. The data obtained was analyzed using SmartPLS software. The results demonstrate a positive correlation between transformational leadership, motivation, career development, work environment, and job satisfaction with employee performance. However, transformational leadership and work environment do not show a significant relationship, either directly or with employee performance, even when mediated by job satisfaction. This research yields managerial implications that can assist BUMN XYZ Tahuna in improving employee performance. This research has several limitations, followed by suggestions for future research.